2010
DOI: 10.1111/j.1553-2712.2010.00959.x
|View full text |Cite
|
Sign up to set email alerts
|

Medication History Taking in Emergency Department Triage Is Inaccurate and Incomplete

Abstract: Objectives: Medication error prevention has become a priority in health care. The Joint Commission recommends that a list of medications, dosages, and allergies be obtained from all patients. The authors sought to determine the accuracy of medication history taking in emergency department (ED) triage. The hypothesis was that there would be significant discrepancies between medications listed in triage and those the patient was actually taking. Methods: This was a prospective, cross-sectional survey of adult pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 8 publications
5
24
0
Order By: Relevance
“…Previous studies have shown that one or more medication discrepancies occur in EDs in 37–87% of individuals . The current study found a proportion (62%) in the preintervention measurement phase that lies within this range.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Previous studies have shown that one or more medication discrepancies occur in EDs in 37–87% of individuals . The current study found a proportion (62%) in the preintervention measurement phase that lies within this range.…”
Section: Discussionsupporting
confidence: 63%
“…Because many people are hospitalized acutely through the emergency department (ED), medication history taking starts there and should be performed adequately, yet several studies show that medication history lists obtained in EDs are not accurate. One or more discrepancies occurred in 37–87% of participants …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Medication histories obtained from triage or from electronic medical record are notoriously inaccurate and should be confirmed with the caregiver or their pharmacy. 137,138 A history of any recent changes or additions to the patient’s home medication regimen should be elicited as well as increased dosages; the clinician should determine if these changes are temporally related to the development of symptoms. In addition to prescribed medications, history of taking over the counter medications and alternative medications should also be obtained.…”
Section: The Diagnostic Evaluation Of Patients With Acute Brain Dysfumentioning
confidence: 99%
“…Emergency nurses are exposed to a complex interplay between stress [life-and-death emergencies (Adriaenssens et al 2012), which is the defining characteristic of their job], sleep deprivation and fatigue due to repeated changes in shifts (Shao et al 2010). Work-related exhaustion can lead to various physical and psychological symptoms (Shao et al 2010) and delayed decision-making, including making treatment or medication errors (Hillin and Hicks 2010;Mazer et al 2011). Moreover, prolonged stress exposes emergency nurses to a higher risk of multiple diseases (Cohen et al 2007;Shao et al 2010), predominantly systemic inflammation (Black 2002;Elenkov et al 2005), metabolic disorders (Pervanidou and Chrousos 2012) and coronary heart disease (Cohen et al 2007;Proietti et al 2011).…”
Section: Introductionmentioning
confidence: 99%